Loss of G-protein coupled receptor 68 in hematopoietic tissues enhances long-term hematopoietic stem cell function upon aging - Xiaofei He; Caleb Hawkins; Lauren Lawley; Tra Mi Phan; Isaac Park; Nicole Joven; Shanshan Shi; Jing Fang (Stem Cell Research & Therapy)
Abstract Background G-protein coupled receptor 68 (Gpr68) was enriched in long-term hematopoietic stem cells, indicating a potential role of Gpr68 in the HSC function. However, there is no significant phenotype in the HSC biology of Gpr68 whole-body KO mice, which may be counteracted by compensation. To study an intrinsic function of Gpr68 in hematopoiesis, Gpr68flox/flox;Vav-cre+ mouse model where the Gpr68 gene was specifically deleted in hematopoietic cells was generated and monitored here (C57BL/6 J genetic background). Methods We used complete blood counting and flow cytometry to determine the number and frequency of mature cells in normal hematopoiesis. We evaluated the number and function of stem cells after competitive bone marrow transplantation using cell surface immune markers. Biological functional experiments were used to explore the related cellular mechanisms. Results Apart from a slightly increased megakaryocyte erythroid progenitor subpopulation, the number of hematopoietic stem and progenitor cells was unaltered in young and mid-aged Gpr68flox/flox;Vav-cre+ mice compared with age-matched Vav-cre+ mice. However, the stem cell function was enhanced in mid-aged Gpr68flox/flox;Vav-cre+ mice, represented by increased donor-derived chimerism compared with age-matched Vav-cre+ mice. As enhanced chimerism was traced to LT-HSC, it revealed an increased LT-HSC activation due to loss of Gpr68 in hematopoietic cells upon aging. Consistently, reduced Gpr68 expression was observed in LT-HSC of old C57BL/6 WT mice compared with young WT mice, validating the specific role of Gpr68 in responding to aging. Besides, the Annexin V staining and active caspases in Gpr68 down-expression mice, i.e., Gpr68flox/flox;Vav-cre+ mice and old C57BL/6 WT mice, were decreased when compared with their control mice, respectively. Conclusion Loss of Gpr68 in hematopoietic tissues enhances LT-HSC function upon aging by inhibiting a cell apoptosis. Graphical abstract